LEGAL THEMES IN THE MAQAMAS OF AL-HARIRI (1054 – 1122) - MICHALSKI, Marcin (Comparative Legilinguistics, 2009)
The paper deals with legal themes used by al-Hariri (1054-1122) in his Maqamas, which portray various social situations typical of the Arab world of the author’s time. This genre, characterized by ornate form and jocular contents, is a good tool of criticism of social phenomena like Islamic law or its language. Al-Hariri bases some of his Maqamas on the ambiguity of the language of law, by which he consciously shows that such ambiguity exists. He also presents some cases examined by judges, including a charge of plagiarism, which at that time was not considered a legal matter.